2017
DOI: 10.3847/1538-4357/aa74ea
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Massive Star-forming Galaxies in Cluster Cores Drives Gas-phase Metallicity Gradients: The Effects of Ram Pressure Stripping

Abstract: Recent observations of galaxies in a cluster at z = 0.35 show that their integrated gas-phase metallicities increase with decreasing cluster-centric distance. To test if ram pressure stripping (RPS) is the underlying cause, we use a semi-analytic model to quantify the "observational bias" that RPS introduces into the aperture-based metallicity measurements. We take integral field spectroscopy of local galaxies, remove gas from their outer galactic disks via RPS, and then conduct mock slit observations of clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 90 publications
(149 reference statements)
1
6
0
Order By: Relevance
“…Observations show that environmental processes are mostly effective for galaxies with M * < 10 10 M ⊙ /h (Peng et al 2010). Gupta et al (2017) shows that star formation suppression in the galactic outskirts due to ram pressure stripping (RPS) can not directly produce a significant enhancement in the SFR-weighted metallicity. However, a relative increase in the metallicity of cluster galaxies compared to field galaxies due to suppression of pristine gas inflow by RPS can not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Observations show that environmental processes are mostly effective for galaxies with M * < 10 10 M ⊙ /h (Peng et al 2010). Gupta et al (2017) shows that star formation suppression in the galactic outskirts due to ram pressure stripping (RPS) can not directly produce a significant enhancement in the SFR-weighted metallicity. However, a relative increase in the metallicity of cluster galaxies compared to field galaxies due to suppression of pristine gas inflow by RPS can not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…), and it is consistent with the mechanism of outside-inward stripping, whereby the most distant, lowest metallicity gas from the galaxy is stripped first, followed by subsequently higher metallicity gas closer to the centre. In fact, semianalytic models of galaxies in clusters (Gupta et al 2017) have invoked outside-in gas stripping to explain, at least partially, the cluster scale (integrated) metallicity gradients observed in galaxy clusters (see e.g. Ellison et al 2009).…”
Section: Star Forming Knotsmentioning
confidence: 99%
“…For galaxies in the Coma cluster ( = 0.023), Carter et al (2002) find a gradient in the Mg 2 and ⟨Fe⟩ indices, which they attribute to pressure confinement of the supernova ejecta by the ICM (also Pasquali et al, 2012). Their suggestion is loosely supported by the ram-pressure stripping (RPS) model of Gupta et al (2017), who show that gas removal by RPS will primarily remove lowmass cluster galaxies from the star-forming population, leading to a cluster-scale metallicity gradient of -0.03 dex Mpc −1 at = 0.35. Gupta et al (2017), therefore hypothesize that RPS is insufficient in explaining the observed Z gradient in = 0.35 cluster, which would require "self-enrichment due to gas strangulation".…”
Section: Introductionmentioning
confidence: 96%
“…Their suggestion is loosely supported by the ram-pressure stripping (RPS) model of Gupta et al (2017), who show that gas removal by RPS will primarily remove lowmass cluster galaxies from the star-forming population, leading to a cluster-scale metallicity gradient of -0.03 dex Mpc −1 at = 0.35. Gupta et al (2017), therefore hypothesize that RPS is insufficient in explaining the observed Z gradient in = 0.35 cluster, which would require "self-enrichment due to gas strangulation". In a study of galaxies in the nearby universe, Hughes et al (2013) came to similar conclusions by studying the oxygen abundances and HI gas mass and gas fraction in 260 star-forming galaxies.…”
Section: Introductionmentioning
confidence: 98%